A scientific-didactic analysis of school manuals: a study based in the " Tectonic Plates" theme - S. Amoêda (2008)
The evaluation issue on school textbooks has been widely disseminated in Portugal because, inaddition to assessing the quality of the manual and its use, it requires a critical look of the scientific and didacticapproaches of the educational contents of the program. On the other hand, the curriculum orientations proposedby the Ministry of Education in Portugal indicated an increasing, and almost inevitable, integration of theTechnologies of Information and Communication in the school environment. Because the school-time for theexecution of the programmatic contents is limited, it increases the need of the school books to diffuse a list ofsites in the Portuguese language or to complement them with interactive CD-ROM's, which would help in theknowledge construction and in the skills development. This paper aimed to analyze the tectonic plate's themeapproach in school books from the 10th grade High School, (intended to 15 and 16-years old students) inPortugal, according to two variables - scientific and didactic. The content analysis conducted has shown that,even though the analyzed manuals followed a satisfactory approach of the educational content program, inscientific terms, it does not provide multimedia support and referential websites in the Portuguese language islimited.